High rate of unemployment among graduates in Malaysia / Tengku Amer Ikhmal Tengku Kamarul Bahrim…[et al.] - Tengku Kamarul Bahrim, Tengku Amer Ikhmal; Hassan Azahari, Hidayati Illiana; Zulkarnal, Nur Aqilah Amani; Sallehhudin, Nur Azzah; Mohd Yusop, Rashidah (Faculty of Communication & Media Studies, 2019)
The graduate unemployment rate is one of the current issues being discussed by higher education scholars. College and university students often face unemployment after spending their valuable time and money in order to receive educational advantages. This study was conducted to examine the factors on why fresh graduates facing a high rate of unemployment in Malaysia as this issue has indirectly affected the graduates as well as the development of Malaysia where the unemployed graduates probably tend to do crimes as their initiative to survive in this era especially with the unstable economy in Malaysia. Apart from that, the graduates’ mental health could also affected in the process of their transition from university to the labour market. Plus, a marriage institution might be affected as well as there will be no financial support provided if the graduates are unemployed. The researchers use in-depth interview in order the get the specific analysis of the unemployment phenomena. The findings of this study shows that factors such as lack of skills, demanding attitude and unstable economic does contribute to the high rate of unemployment among graduates. Apart from that, the unemployment also affected the graduates and development of Malaysia where the criminal activities increased, graduates faced mental health issue and harm the family institutions. The findings also shows that serious actions from the government as well as the graduate itself need to be taken in order to reduce the issue of unemployment in Malaysia.